PENGARUH SOSIALISASI, SANKSI, DAN PENDAPATAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (Jurnal Riset Manajemen dan Akuntansi, 2023)
This research was conducted in order to measure the amount of sanctions, socialization, and income of taxpayers affecting taxpayer compliance in paying land and building taxes. Using a descriptive qualitative method and a Likert scale as a measurement, the research data was collected through questionnaires distributed. For data processing, the authors chose SPSS and 36 Pondok Suri housing residents as respondents. From the results of the study, the authors stated that only sanctions and income partially affected taxpayer compliance with a sanction t-test value of 4.747 and a significance of 0.000. Income t test is 2.347 with a significance of 0.026. While the socialization t test is only –2.342 with a significance of 0.025. In addition, the F test 17.147 > F table 2.86 with a significance of 0.000 indicates that the three independent variables affect taxpayer compliance simultaneously